The relationship between motivation and learning strategy use in English of students at a college in Can Tho city : - Nguyễn, Thị Thuý Hằng (Đại học Cần Thơ, 2011)
The study investigated the English language learning motivation, learning strategies, and the correlations between these two variables among students at a college in Can Tho City. The results of the study showed that the most frequent type of motivation was extrinsic motivation; and the most frequently used strategy category was meta-cognitive while the least was social strategy